Short Communication: Oviposition and chlorosis scoring for early screening of chili resistance to whitefly (Bemisia tabaci) - TENGKU LAILA KAMALIAH; MUHAMAD SYUKUR; SOBIR SOBIR; AWANG MAHARIJAYA; PURNAMA HIDAYAT (Society for Indonesian Biodiversity, 2025)
Abstract. Kamaliah TL, Syukur M, Maharijaya A, Hidayat P. 2025. Short Communication: Oviposition and chlorosis scoring for early screening of chili resistance to whitefly (Bemisia tabaci). Biodiversitas 26: 6410-6416. Bemisia tabaci is a major pest of chili. The objective of this study was to establish a rapid screening technique for chili resistance, based on oviposition and chlorosis parameters. The research was conducted in the plastic houses of Sinar Alam Sari, Cibeureum, Bogor, Indonesia, from June to December 2021, using a randomized complete block design with three replications. Eight chili genotypes (Capsicum annuum cv. Adelina, Anies, C12, Kencana, Laris, Landung, Ungara, and Yuni) were infested with four non-viruliferous whiteflies per leaf in a no-choice test. The number of eggs and early instar nymphs was counted on the 7th and 10th days, respectively, while chlorosis was scored on the 21st day after infestation. Results showed significant differences among genotypes. Landung and Yuni were the most susceptible, with the highest egg counts (52.83 and 51.17 per leaf), nymph counts (48.17 and 47.50), and severe chlorosis (score 3-4). Ungara was highly resistant, with the lowest egg (9.00) and nymph counts (4.83), and minimal chlorosis (score 1-2). A strong correlation was observed between high egg/nymph numbers and severe chlorosis, which was objectively validated by RGB image analysis showing a near-perfect negative correlation between chlorosis score and the NGRDI (-0.995). The study concludes that combining egg count and chlorosis scoring—supplemented by digital RGB/NGRDI validation—provides a novel, simple, efficient, and reliable method for the early screening of chili resistance to B. tabaci, offering an integrated method of breeding programs.